DIGITAL MARKETING DAN PERSONAL SELLING SEBAGAI DETERMINAN KEPUTUSAN PEMBELIAN KONSUMEN TOKO KOSMETIK NEW MEGAH JAYA - Hendrayana (PT. ABIG RIZKY PUBLISHER, 2025)
This study aims to analyze the effect of digital marketing and personal selling on consumer purchasing decisions at New Megah Jaya Cosmetic Store, Sukabumi. The research background is driven by digital transformation that has reshaped marketing interactions, as well as fluctuations in the store’s sales performance. The study employs a quantitative approach with a causal associative research design. A sample of 89 respondents was selected using simple random sampling from a total population of 845 consumers during the period January to August 2025. Data were collected through a structured questionnaire and analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that digital marketing and personal selling simultaneously have a significant effect on purchasing decisions, with a contribution of 61.9%. Partially, both variables have a positive and significant influence, with digital marketing identified as the most dominant factor affecting consumer decisions (β = 0.636). These findings suggest that the combination of the broad reach of digital technology and persuasive interpersonal communication is highly effective in influencing consumers in the cosmetic industry. In conclusion, the integration of modern and conventional marketing strategies is crucial to enhancing competitiveness and achieving sustainable sales performance for the store.